Assessment of the wintering area of Red Knots in Maranhão, northern Brazil, in February 2005 - Baker,Allan J. (2005)
To assess population size and the conservation status of the Red Knot Calidris canutus rufa population in Maranhão, N Brazil, an aerial census and field studies were conducted in February 2005. The aerial count showed a population of 7,575 Knots, which is down about 600 from a previous census in the 1980s. However, the count for all shorebird species combined was only 24,000 compared to 198,600 in the 1980s, paralleling a world-wide trend of population decline in shorebirds. Resightings of colour-banded knots confirmed that this is a separate population from the larger wintering population in Tierra del Fuego. All species of shorebirds captured in Maranhão were found to be infested with feather lice and mites. Body masses of knots in Maranhão were significantly lower than in Tierra del Fuego, and about half the birds were below the hypothesized fat-free mass of the species. Blood and feather samples were taken from 38 Knots for subsequent assessment of virus loads, and for detecting sites where primary feather moult had occurred. This will enable us to establish whether significant mortality is associated with pathogen loads and the energetic demands of delayed moulting. The small size of the Maranhão population and the loss of another 13,000 knots this winter from the Tierra del Fuego population means that both are now endangered. Brochures on the need for Red Knot conservation were designed and printed, and have been circulated among fishing communities and school classes in Maranhão.